Cholest-4-en-3-one attenuates TGF-β responsiveness by inducing TGF-β receptors degradation in Mv1Lu cells and colorectal adenocarcinoma cells. (4th March 2017) - Chen, Chun-Lin; Wu, Deng-Chyang; Liu, Min-Yun; Lin, Ming-Wei; Huang, Hung-Tu; Huang, Yaw-Bin; Chen, Li-Chai; Chen, Yu-Yu; Chen, Jih-Jung; Yang, Pei-Hua; Kao, Yu-Chen; Chen, Pei-Yu
Abstract: Purpose: The transforming growth factor-beta (TGF-β) pathway is an important in the initiation and progression of cancer. Due to a strong association between an elevated colorectal cancer risk and increase fecal excretion of cholest-4-en-3-one, we aim to determine the effects of cholest-4-en-3-one on TGF-β signaling in the mink lung epithelial cells (Mv1Lu) and colorectal cancer cells (HT29) in vitro . Methods: The inhibitory effects of cholest-4-en-3-one on TGF-β-induced Smad signaling, cell growth inhibition, and the subcellular localization of TGF-β receptors were investigated in epithelial cells using a Western blot analysis, luciferase reporter assays, DNA synthesis assay, confocal microscopy, and subcellular fractionation. Results: Cholest-4-en-3-one attenuated TGF-β signaling in Mv1Lu cells and HT29 cells, as judged by a TGF-β-specific reporter gene assay of plasminogen activator inhibitor-1 (PAI-1), Smad2/3 phosphorylation and nuclear translocation. We also discovered that cholest-4-en-3-one suppresses TGF-β responsiveness by increasing lipid raft and/or caveolae accumulation of TGF-β receptors and facilitating rapid degradation of TGF-β and thus suppressing TGF-β-induced signaling. Conclusions: Our results suggest that cholest-4-en-3-one inhibits TGF-β signaling may be due, in part to the translocation of TGF-β receptor from non-lipid raft to lipid raft microdomain in plasma membranes. Our findings also implicate that cholest-4-en-3-one may be further explored for its potential role in colorectal cancer correlate to TGF-β deficiency.